Adipose tissue in halal meat can be a source of adiponectin protein - Azahari , Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani (2016)
The objective of this study was to isolate and quantify total protein and adiponectin from halal meat sources of chicken, beef and lamb adipose tissues. Abdominal adipose tissues were removed from chicken, beef and lamb rinsed with ice-cold phosphate-buffered saline (PBS) solution. Delipidation of aforementioned tissues were prepared by chloroform/methanol extractions modified from Bligh and Dyer method. The protein concentration was determined by using Protein Assay Bicinchoninate Kit. After that, quantification of the adiponectin protein in chicken, beef and lamb tissues were assessed by using ELISA assay kit according to manufacturer’s instructions. The experiment was conducted in triplicates and the results were presented as means ± SD. Results indicate that the extraction of 10 gram subcutaneous adipose tissues from chicken, beef and lamb yielded about 0.1 gram of protein amount which was only 1 % from total tissue mass. The protein concentration in adipose tissue of chicken, beef and lamb were 1.25 ± 0.05, 1.75 ± 0.05 & 2.53 ± 0.07 mg/ml respectively. Then, Adiponectin levels in chicken, beef and lamb were 158 ± 4.5 ng/ml, 24 ± 0.5 µg/ml and 37 ± 0.98 ng/ml respectively. Adiponectin is one of the promising candidate for future pharmacological treatment strategies for insulin resistance and metabolic diseases.